IMPROVEMENT OF SINGING VOICE THROUGH EXPERIENTIAL LEARNING MODEL WITH PIANIKA IN FIFTH GRADE OF SDN 1 BANDUNG KEBUMEN IN ACADEMIC YEAR OF 2019/2020 - Nurjihan Hasanah; Tri Saptuti Susiani; Joharman Joharman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The objectives of the research were: (1) to describe the steps of Experiential Learning model with pianika, (2) to describe improvement of students' singing voice, and (3) to analyze the obstacle and solution in applying experiential learning model with pianika in improving students' singing voice. It was a collaborative classroom action research conducted in three cycles. Each cycle consisted of planning, implementation, observation and reflection. The subjects were 32 students and the teacher of fifth grade of SDN 1 Bandung Kebumen. Data collection techniques were observation, interview, and tests. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results showed that: (1) the steps to Experiential Learning model with pianika were: a) Concrete Experience, b) Reflective Observation, c) Abstract Conceptualization, and d) Active Experimentation; (2) Experiential Learning model with pianika improved students' singing voice. It was proven by average of mastery learning in singing vocal. There were 71.88% in the first cycle, 79.69% in the second cycle, and 84.38 % in the third cycle; (3) the obstacle was that some students had difficulty in developing expressive performance while they were practicing singing with pianika. The solution to overcome the obstacle was that the teacher encouraged the students by giving examples sing expressively through the meaning of song and stay focused during singing. It concludes that the application of Experiential Learning model with pianika improves students' singing voice in fifth grade of SDN 1 Bandung Kebumen in the academic year 2019/2020.